2002
DOI: 10.1016/s0925-4927(02)00025-2
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala–hippocampal shape differences in schizophrenia: the application of 3D shape models to volumetric MR data

Abstract: Evidence suggests that some structural brain abnormalities in schizophrenia are neurodevelopmental in origin. There is also growing evidence to suggest that shape deformations in brain structure may reflect abnormalities in neurodevelopment. While many magnetic resonance (MR) imaging studies have investigated brain area and volume measures in schizophrenia, fewer have focused on shape deformations. In this MR study we used a 3D shape representation technique, based on spherical harmonic functions, to analyze l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
76
0
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(86 citation statements)
references
References 93 publications
8
76
0
2
Order By: Relevance
“…Using a deformable shape method, which combines geometric properties of hippocampal boundaries, statistical characterization of normal shape variation, and manually defined boundary points, Shen et al 137 demonstrated excellent agreement between automatic and manual volumetrics of the hippocampus. Shenton et al 138 have used an active, flexible deformable shape model for the automatic volumetrics of the amygdala-hippocampal complex to investigate volumetric changes in schizophrenia. These automated methods mark the onset of a new era in structural neuroimaging.…”
Section: Discussionmentioning
confidence: 99%
“…Using a deformable shape method, which combines geometric properties of hippocampal boundaries, statistical characterization of normal shape variation, and manually defined boundary points, Shen et al 137 demonstrated excellent agreement between automatic and manual volumetrics of the hippocampus. Shenton et al 138 have used an active, flexible deformable shape model for the automatic volumetrics of the amygdala-hippocampal complex to investigate volumetric changes in schizophrenia. These automated methods mark the onset of a new era in structural neuroimaging.…”
Section: Discussionmentioning
confidence: 99%
“…There have been many approaches to shape characterization, which has resulted in a specialized area of computer science expertise (recently review by Shenton et al [2002]). Quantitative descriptions of shape have included approaches such as the generation of skeletons or a medial axis to characterize features of a shape (Golland et al 1999).…”
Section: Mri Methodsmentioning
confidence: 99%
“…Furthermore, the quantitative analysis of shape, we believe, provides a complementary approach to the quantitative analysis of volume of structural brain abnormalities in neuropsychiatric disorders, because shape changes might occur with little or no change in volume. As suggested by prior shape studies of the hippocampus in adult schizophrenia (Csernansky et al 1998;Shenton et al 2002;Wang et al 2001), quantitative shape analyses might be more sensitive than volumetric measures for detecting small changes in volume or volume changes that might be restricted to subregions of brain structures. Here, we use an approach that is conceptually less complex than prior methods (e.g., Csernansky et al 1998;Shenton et al 2002;Thompson et al 2000;Wang et al 2001) for measuring the shape of brain structures and have been able to detect group differences that complement our prior volumetric findings.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, relatively few pathology-specific probability maps have been created ; Thompson et al, 1997). Instead of using probability maps, pathology-specific variations have been investigated using shape analysis of specific ROIs (Csernansky et al, 1998;Shenton et al, 2002), but shape analysis does not provide information on spatial distribution, especially the relative location of ROIs together with neighboring brain regions.…”
Section: Introductionmentioning
confidence: 99%